Tuning the student mind : a journey in consciousness-centered education - Beauregard, Molly, 1965- (State University of New York, 2020)
"How can we rethink teaching practices to include and engage the whole student? What would student experience look like if we integrated silence and feeling with empirical analysis? Tuning the Student Mind is the story of one teacher's attempt to answer these questions by creating an innovative college course that marries the spiritual and the theoretical, integrating meditation and self-reflection with more conventional academic curriculum. The book follows Molly Beauregard and her students on their intellectual and spiritual journey over the course of a semester in her class, "Consciousness, Creativity, and Identity." Interweaving personal stories, student writing, and Beauregard's responses, along with recommendations for further reading and a research appendix, it makes the case for the transformative power of consciousness-centered education. Written in a warm, engaging voice that reflects Beauregard's teaching style, Tuning the Student Mind provides an accessible, step-by-step template for other educators, while inviting readers more broadly to reconnect with the joy of learning in and beyond the classroom"--